Evaluation of a Workplace-Based Migraine Education Program. Issue 8 (August 2016) - Burton, Wayne N.; Chen, Chin-Yu; Li, Xingquan; McCluskey, Maureen; Erickson, Denise; Schultz, Alyssa B.
Abstract : Objective: Migraine affects approximately 10% of working-age adults and is associated with increased health care costs, absenteeism, and presenteeism in the workplace. A migraine education program was offered to United States employees of a global financial services organization. Methods: Two hundred forty three employees (46% response rate) completed both a baseline and 6-month follow-up migraine questionnaire. The program included webinars, E-mailed educational tips, and intranet-based resources. Results: No change was found in the frequency of migraines but improvements were observed in the severity, workdays missed, effectiveness at work during migraine, and work/activity limitations. Participants reported taking action to identify and reduce migraine triggers. Conclusions: A worksite disease education program for migraine headache has the potential to significantly impact lost productivity and absenteeism for migraineurs.